O agir e o representar por meio de linguagem: gênero memórias literárias - Souza, Angela Maria Baltieri (2018)
This text discusses the results of a study based on written productions of the genre Literary Memories of the finalists of the Olimpíada de Língua Portuguesa Escrevendo o Futuro – 2014. The objective of this study was to analyze the language in a real life communication and to identify how these authors describe and how they are guided to discuss where they live, including their own experience. An articulation between the Theory of Social Representations and Sociodiscursive Interactionism and the material which gave support to comprehend the possibilities and limitations of both theories. The theme Literary Memories (written production) of students, was to comprehend the images, the discourses and linguistics representations of the written process. Through this Theory of Social Representations, genre studies and Sociodiscursive Interactions, the study with the theme “Where I live” allowed an analyses of the voice of the subject (students), his interpersonal relationship (I/other/world/we/family/community) in the text, considering the processes to the final written production. The use of the software Alceste (Analyse Lexicale par Contexte d. um Ensemble de Segments de Texte)), a program of textual analysis that aims to quantify and extract the most significant structures, supported the analysis of the texts and allowed a deep qualitative and quantitative study. In the qualitative analyses, it was possible a written psychoanalysis. Through this analyses, in two dimensions, it was possible to observe that the student/author brings elements of the past from the other, values the feelings of the time and at the same time talks about the place where he lives prioritizing the subject/author to describe the place where he lives, It values a rural Brazil located in a distant past, far from the childhood of those who are talking about it. It also showed the written production context (physical context and social subjective) of the subject action. The study allows teachers to reflect and discuss on how a written production process about the place where students live, provided by the interviews which were resources from former residents can enhance students´ own experience. Discuss the past of the other, integrating and valuing your own present, considering it while integrating it to the future